2015 IEEE 1st International Workshop on Crowd-Based Requirements Engineering (CrowdRE) 2015
DOI: 10.1109/crowdre.2015.7367582
|View full text |Cite
|
Sign up to set email alerts
|

Social media through the requirements lens: A case study of Google maps

Abstract: Social media serves as an extensive repository of user interaction related to software applications. Users discuss application features and express their sentiments about them in both qualitative (usually in natural language) and quantitative ways (for example, via votes). Further, many social media applications support explicit social networks of users and measures such as user reputation. Naturally, content on social media has the potential to inform requirements engineering. However, models of requirements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…CrowdRE uses different channels to achieve this. Many existing work uses a general purpose media to access a community of crowd, online forums and mobile application marketplaces [29,56,31,35], a few others uses social network tools to access crowd along with LinkedIn [72,22], research workshops [39], mobile stores and twitter [6] [62, 79,91], as in Table 3. Similarly, MuruKannaiah et al [56,57], developed their own crowd requirements research dataset to research user communities and other diverse characteristics of crowd members, which can be used for analysis and prioritization of requirements using Amazon Mechanical Turk, which is a crowd-based platform.…”
Section: Utilities In Crowdrementioning
confidence: 99%
“…CrowdRE uses different channels to achieve this. Many existing work uses a general purpose media to access a community of crowd, online forums and mobile application marketplaces [29,56,31,35], a few others uses social network tools to access crowd along with LinkedIn [72,22], research workshops [39], mobile stores and twitter [6] [62, 79,91], as in Table 3. Similarly, MuruKannaiah et al [56,57], developed their own crowd requirements research dataset to research user communities and other diverse characteristics of crowd members, which can be used for analysis and prioritization of requirements using Amazon Mechanical Turk, which is a crowd-based platform.…”
Section: Utilities In Crowdrementioning
confidence: 99%
“…Numerous studies focused on improving the requirement engineering process by understanding users' perspectives from the reviews on app marketplaces and user forums [9]- [11], [60]. Pagano and Maleej [10] identified the patterns, topics, and quality of user feedback in over one million Apple App Store reviews and studied its impact on the software requirements.…”
Section: B Eliciting Requirements From App Reviewsmentioning
confidence: 99%
“…Pagano and Maleej [10] identified the patterns, topics, and quality of user feedback in over one million Apple App Store reviews and studied its impact on the software requirements. Prior work has shown the importance of user feedback from software forums [9] and social media platforms [11], [19], [60]. Tizard et al [9] analyzed user reviews and feedback from the two product forums (VLC and Firefox) and concluded that product forums are a valuable source of consumer feedback that is essential for the evolution of the product.…”
Section: B Eliciting Requirements From App Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a sense, what we would like to do is to give a mapping from such information to requirement models. In other words, we want to create a requirements-oriented view over the information [16].…”
Section: Introductionmentioning
confidence: 99%